Literasi Keuangan: Investasi Emas Nggak Ada Matinya! - Maria Augustine Graciafernandy; Erlina Dewi Endah Amaliyah; Eko Usriyono; Masine Slahanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Understanding of financial literacy is related to a person's ability to be able to manage his finances, including determining the right investment instrument. The results of the survey to the teachers of SMP Kuncup Melati showed that 70% of the teachers felt that investments could only be made with large capital. This PKM was carried out at SMP Kuncup Melati Semarang by offline meeting and collaborated with PT Pegadaian to explain about gold investment. Gold can be used as an investment tool for novice investors as it tends to be stable and safe. The teachers of SMP Kuncup Melati have been given an understanding of the concept and various types of investment, knowledge of how to choose safe, reliable, and affordable investments. The positive response was seen by the interactive communication between the presenters and the participants. The post-activity questionnaires were filled out, and it showed that the teacher's understanding was increasing. The aim of this PKM is that the teachers' insight will be more open and be more critical to various investment products on the market. Furthermore, it is expected that teachers can participate in spreading knowledge about financial literacy to students and the community.